Tingginya Uang Panai Bugis Sidrap: Mengangkat Derajat Perempuan Atau Membebani Laki-Laki Untuk Menikah? - Almaida, Heny (Fakultas Syariah INSURI Ponorogo, 2023)
Uang panai is spending money for the cost of a Bugis wedding party and it is also one of the traditions in the bridal procession in Bugis society, including in Sidenreng Rappang Regency (Sidrap). However, the phenomenon of the Sidrap Bugis tribe is that the community advertises this panai money at a price that is no longer familiar to the local community or it can be said that the value of panai money is high, so that it makes many Bugis male feel overwhelmed and they feel burdened to marry the Bugis female who they love. There are many assumptions that female who receive high nominal panai money are able to raise their degrees. The purpose of this research is to find out the high panai money of the Sidrap Bugis tribe whether it raises the status of female or actually burdens male to get married. The type of this research is used phenomenological research with a qualitative approach which of course collects data such as observations, interviews and documentations and analyzes data using descriptive data. The conclusion of this research is that the high panai money in the Sidrap Bugis tribe does not raise the status of women but the high panai money actually burdens male to get married.